Clinical profile of users of Peripherally Inserted Central Catheter in a Military Hospital - Furtado Rodrigues, Elaine (2024)
Objective: Analyze the clinical profile of adult patients who have undergone and/or are undergoing the use of a peripherally inserted central catheter during hospitalization. Specific objectives: Examine the indications for the insertion of the peripherally inserted central catheter and the clinical profile of patients using it, and identify complications directly related to its use. Methods: Documentary, descriptive, retrospective study with a quantitative approach, conducted at a Military Hospital in Rio de Janeiro. A total of 162 patients with peripherally inserted central catheter insertion from January 2022 to June 2023 were analyzed.  Results: Prevalence was observed in patients over 60 years old, predominantly male. The prevalent requesting clinic was Trauma-Orthopedics, and the medical diagnosis was surgical wound infection. The most common indication was prolonged antibiotic therapy. The most punctured vein was the Brachial. The majority retained the device for 8 to 20 days, removed after completing the treatment. The most recurring complication was bloodstream infection. Conclusions: The profile of the analyzed patients is consistent with similar studies already published and with the indications for the use of this catheter reported in current guidelines. The reported complications align with those found in the literature.